تحضير ودراسة البنية البلورية للمركب Ca1-xGdx)0.9Sr0.1FeO2.5+& بطريقة محلول -هلام - خضير, الحادة; دبار, إيمان (universty of elouedجامعة الوادي, 2021)
" تم في هذا العمل دراسة مدى تأثير درجة الحرارة على الخواص البنيوية والضوئية للأغشية الرقيقة لكبريتيد الكادميوم المرسبة وفق طريقة الحَمام الكيميائي على ركائز زجاجية. حيث حضرت الأغشية إنطلاقًا من كبريتات الكادميوم ((CdSO4 كمصدر للـ Cdوالثوريا كمصدر للكبريتيدS، مع إستعمال الأمونياك كمعقد للتفاعل. أظهرت نتائج إنعراج الأشعة السينية أن أغشية CdSالمحضرة ذات بنية مكعبة بالإتجاه المفضل (111). أوضحت نتائج UV-Vis أن الأغشية المحضرة ذات نفاذية تقارب% 80، اما الفجوة الطاقية المتحصل عليها فكانت في المجال eV( 2.56- 2.75). كما بينت نتائج FTIR بروز الرابطة ( (Cd-Sفي نطاق التردد 470 cm-1 . ""In this work, the effect of temperature on the structural and optical properties of cadmium sulfide thin films deposited according to the chemical bath method on glass substrates was studied. The chemical bath solutions were prepared from cadmium sulfate (CdSO4) as a source of Cd+2 and thiourea SC(NH2)2 as a source of S-2, with ammonium hydroxide (NH3, H2O) as a complexing agent. The X-ray diffraction results showed that the prepared CdS films have a cubic structure with (111) preferred orientation. UV-Vis results showed that All the prepared films exhibit a high transmittance in the visible range, it is in order of 80%, the obtained values of the optical gap are between 2.56 and 2.75 eV. The FTIR results also showed the emergence of the (Cd-S) bond in the frequency band 470 cm-1. "
مذكرة مستر فيزياء
Keywords: أغشية رقيقة، الخواص البنيوية، الخواص الضوئية، كبريتيد الكادميوم، الحمام الكيميائي، إنعراج الأشعة السينية، UV-Vis ،FTIR .; Thin films, structural properties, optical properties, cadmium sulfide, X-ray diffraction, UV-Vis, FTIR.